DETERMINATION GENETIC DIVERSITY OF INBRED LINES AND HYBRIDS OF MAIZE USING ISSR TECHNIC - & Abdul -Hamed, Amoon (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was carried out in the biotechnology laboratories of the Seed Inspection and Certification Department - Ministry of Agriculture during 2019, to study the relation among molecular five inbred lines with hybrid crosses of maize. to estimate the genetic diversity and determine the degree of genetic similarity among them using the ISSR based on PCR technic with 6 primers. All primers produced 79 bands at a rate of 13.2 bands per primer. The number of amplified bands ranged from 10 to the primer UBC 835 and 16 in the UBC 897, with a molecular length ranged between 100 - 1700 bp. The total number and percentage of polymorphic bands was 71 and 90% respectively. The primers UBC 856 and UBC 866 the highest percentage of had polymorphic bands of 100%. While the UBC 835 showed the lowest (70%). The highest efficiency and specificity were 12.7% and 9.9% respectively in UBC835. Based on molecular marker data and genetic similarity using the UPGMA method in establishing the dendrogram, the study showed that genetic similarity between the inbred lines ranged from 0.105 to 0.40, the highest (0.40) between the two strains BK121 and Zm6 , While the lowest degree of similarity (0.105) was between the two strains BK121 and ART-817 .